Gauging the horizontality of community philanthropy organizations: The development and validity testing of an instrument - Wilkinson-Maposa, Susan (Department of Sociology, 2016)
This thesis sets out to develop an instrument to gauge the behaviour of a community philanthropy organization (CPO) and then to test its validity. Using both quantitative and qualitative methods, the Horizontality Gauge (HG) offers a process by which organizations can assess the extent to which their behaviour favours either the ways in which the international aid system prefers to work (with an exogenous orientation) or those of the community it serves (taking an endogenous approach), which is the orientation professed in its model. When applied, the instrument is intended to facilitate self-correction, with the potential to contribute to organizational development (OD) and improved performance. The instrument is made up of a questionnaire and a group interview. It produces data in the form of Likert scale scores (quantitative) as well as qualitative evidence in the form of narrative illustrations of organizational behaviour and respondent judgement of scores. The thesis draws on the concepts of the philanthropy of community (PoC) theory, in particular those related to the norms of self-help and reciprocity among the poor in southern Africa, in the context of the four elements of an organization as described in the work of Wilkinson-Maposa and Fowler (2009), and Porras and Hoffer (1986). It also adapts and applies the multi-level systematic framework for validating a research instrument developed by Adcock and Collier (2001), as modified by Lutz (2012). The secondary contribution of this study involves the refinement of the PoC theory and the further testing of an existing framework in the emerging field of validation in mixed methods research (MMR). The HG was tested using the cases of five CPOs in South Africa. The findings show that it satisfies the assessment validation criteria of trustworthiness offered by Lincoln and Guba (1985) and researchers, donors and community philanthropy organizations can therefore use it with confidence and assurance. However, further refinements of the instrument are indicated. Specifically, insights problematize the vertical (the exogenous) in light of the domestication of funding in South Africa and call into question the ease with which the user can access and interpret the gauge as presented visually on a behaviour arc.